Pengaruh Lingkungan Kerja Dan Gaya Kepemimpinan Situasional Terhadap Niat Mengundurkan Diri (Turnover Intention): Studi Pada Karyawan Kantor Pusat PT. Bumitama Gunajaya Agro - Salfadila, Nisrina; Winanto, Sujoko; Maulidizen, Ahmad (BADAN PENERBIT STIEPARI PRESS, 2022)
Human resources are a very important resource for the success and existence of a company in achieving its goals. However, it should be balanced with the maintenance of employees so that existing resources feel comfortable in the company. A company that can make its resources last is a challenge because of the many other factors influencing employees to leave, such as the work environment and the leadership applied. Based on this, the researcher wishes to conduct a study to determine and explain the effect of the work environment and situational leadership style on the intention to resign employees at PT. Bumiatama Gunajaya Agro. This research is classified into quantitative types with descriptive nature. The tests were carried out using simple linear regression analysis techniques, multiple linear analysis, and classical assumption tests. A simple random sampling technique was used to determine the number of samples; with the slovin formula obtained, the respondents amounted to 81. The data processing device in this study uses IBM SPSS Statistics Ver. 25. The analysis results in this study indicate that the work environment and leadership style variables have a negative and significant effect on employee resignation intentions. The work environment and situational leadership style variables negatively and significantly affect employees' intention to resign. It can be proven by the significance level of each below 0.05, which is 0.000. The suggestions from researchers for PT. Bumitama Gunajaya Agro pays more attention to the rights and opportunities fully and fairly through its employees' situational leadership style and work environment, especially the equipment used to support the work, increase employee loyalty, and reduce the level of intention to resign employees